Improving Very High Plastic Clays with the Combined Effect of Sand, Lime, and Polypropylene Fibers - Meddah, Abdelaziz; Goufi, Abd Elmalik; Pantelidis, Lysandros (My University, 2022)
Featured Application: This work suggests a stabilization technique for improving the engineering properties of problematic soils (i.e., very high plastic clays of low strength and high deformability) based on the combined effect of sand, lime, and polypropylene fibers. The proposed stabilization technique proved to be very effective, largely increasing the unconfined compressive strength and ductility of clay soils. Improving the mechanical properties of low-strength soils (e.g., high plasticity clays) is one of the main branches of geotechnical engineering. The adoption of stabilization techniques for ensuring that structures will be founded on an adequately strong soil base is a common practice. Stabilization techniques for clay soils may include inert materials (cohesionless soils), chemical substances (cement, lime, or industrial additives), or the use of randomly distributed fibers. While all of these additives are added to low-strength soils by mixing, the question remains whether an optimal combination of stabilization techniques can be achieved for maximizing soil strength. Besides, each one of these additives contributes to an increase in soil strength in a different manner (soil replacement, chemical bonding of soil particles, and soil reinforcement respectively), while, according to the literature, each technique has its limitations. The latter refers to a limited effect on strength improvement and a maximum possible percentage, beyond which an additive has an adverse effect on strength; it also refers to other factors, such as brittleness failure, material availability, overall cost, and environment-related issues. Hence, in the present study, the efficiency of improving the basic geotechnical properties of a very high plasticity clay (liquid limit ωl = 86%) with a coupled effect between dune sand, lime, and polypropylene (PP) fibers has been investigated. The samples prepared by combining the three aforementioned soil improvement techniques were compared in terms of plasticity, compaction characteristics, unconfined compressive strength (UCS), and California Bearing Ratio (CBR) index. The experimental results show that the combination of these additives may lead to a considerable improvement in the strength and ductility of soils, even with a small amount of lime additive. Also, it was observed that 20% of sand, 3.4% of lime and 0.9% of fibers (by wt%) offers the best performance in terms of strength improvement for the clay tested (i.e., 12.75 times improvement compared to the untreated clay).
Keywords: Stabilization; Reinforcement; High plastic clays; Lime; PP fibers